2008
DOI: 10.1677/erc-08-0136
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin promotes in vivo metastasis of prostate cancer cells by altering cell signaling, adhesion, and inflammatory pathways

Abstract: Expression of calcitonin (CT) and its receptor (CTR) is elevated in advanced prostate cancer (PC).Although the significance of CT-CTR axis in PC cell growth, invasion, and epithelial to mesenchymal transition has been established, its role in tumor metastasis has not been examined. To examine the role of CT-CTR axis in tumor metastasis, we employed stable CT-CTR activated and silenced system of three PC cell lines, LNCaP cells that lack endogenous CT, PC-3 cells that lack endogenous CTR, and PC-3M cells that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 42 publications
(48 reference statements)
4
30
1
Order By: Relevance
“…Early studies suggested that NEPCa might secrete different kinds of cytokines and peptides, including bombesin, calcitonin, parathyroid hormone-related protein (PTHrP), serotonin and VEGF, to stimulate progression in its neighboring PCa (9–11, 31, 32). We first compared the expression of some cytokines and peptides related to p38/MAPK signals between LNCaP and NE1.3 cells (3337).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies suggested that NEPCa might secrete different kinds of cytokines and peptides, including bombesin, calcitonin, parathyroid hormone-related protein (PTHrP), serotonin and VEGF, to stimulate progression in its neighboring PCa (9–11, 31, 32). We first compared the expression of some cytokines and peptides related to p38/MAPK signals between LNCaP and NE1.3 cells (3337).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of NEPCa has been regarded as not only a sign for PCa progression, but also an inducer of growth and survival for the neighboring PCa by secreting a variety of cytokines and peptides (9–11, 31, 32). For example, NEPCa secrete several neuropeptides, including bombesin, which can act as a mitogen in PCa tumors via activation of the transcription factor Elk-1 and the immediate early gene c-fos (46).…”
Section: Discussionmentioning
confidence: 99%
“…The SOI was performed under Ketamin/Xylazine anesthesia as previously described (Chien, et al 1999; Shah, et al 2009b; Shah, et al 2008). In brief, tumor cell suspensions (1×10 6 cells/20μl) were injected into the dorsal prostate, the mice were maintained on the laboratory diet ad libitum for up to sixty days, and were regularly monitored for tumor growth/metastasis with fluorography using Kodak 4000 MM imaging station (Thomas et al 2006).…”
Section: Methodsmentioning
confidence: 99%
“…These include AAV2-maspin to LNCaP and DU145 prostate cancer tumors [144]; AAV2-nm23H1 to SW626-M4 metastatic ovarian cancer tumors [145]; AAV2-HGFK1 (kringle 1 domain of human hepatocyte growth factor) to CT26 and Lovo colorectal carcinoma tumors [146]; AAV2-encoded anti-calcitonin ribozymes to an orthotopic implantation model and a transgenic model of prostate cancer [147]; AAV2-4EBP1 (eukaryotic translation initiation factor 4E-binding protein 1) to a K-ras LA1 lung cancer model [148]; AAV2-mediated delivery of the chemokine receptor CXC chemokine receptor 2 (CXCR2) C-tail sequence to an HPAC pancreatic tumor model [149]; AAV1 delivery of IL-24 and apoptotin to a HepG2 liver cancer model [150]; AAV2-TAP (alpha-tocopherol-associated protein) to PC-3 and LNCaP prostate cancer tumors [151]; delivery of trichosanthin, packaged in AAV3-S663V+T492V vectors, to HuH7 hepatocellular carcinoma (HCC) tumors [66]; AAV2-decorin to a U87MG glioblastoma multiforme model [152]; AAV2-cathelicidin to HT-29 colon cancer tumors [153]; AAV8-mediated delivery of Niemann-Pick type C2 (NPC2) to the N-methyltransferase knockout (Gnmt−/−) transgenic spontaneous HCC model [154]; and AAV9-mediated delivery of human Mullerian inhibiting substance (MIS, albumin leader Q425R MIS (LRMIS)) in a xenograft model of ovarian cancer [155]. Additionally, groups have delivered the p53 tumor suppressor gene, commonly mutated in cancerous cells, using AAV2 vectors to bladder cancer cells [156] and non-small cell lung cancer cells [157] in vitro and to an H358 bronchioalveolar carcinoma tumor model in vivo [158].…”
Section: Aav Delivery Of Therapeutic Payloads In Preclinical Models Omentioning
confidence: 99%